2021
DOI: 10.3390/ijms23010414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nanoparticle Exposures on the Tomato Bacterial Wilt Disease Control by Modulating the Rhizosphere Bacterial Community

Abstract: Ralstonia Solanacearum is one of the most infectious soil-borne bacterial plant pathogens, causing tomato bacterial wilt (TBW). Nanotechnology is an emerging area of research, particularly the application of nanoparticles (NPs) as nanopesticides to manage plant disease is gaining attention nowadays. However, the interaction between NPs and rhizosphere bacterial communities remains largely elusive. This study indicated that metal NPs (CuO, ZnO, and FeO) reduced the incidence of bacterial wilt to varying degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The bioinformatics analysis of the microbiome was accomplished according to our previous study [ 18 ]. In brief, sequence raw data were demultiplexed with the demux plugin, then primers were trimmed with the cut adapt tool.…”
Section: Methodsmentioning
confidence: 99%
“…The bioinformatics analysis of the microbiome was accomplished according to our previous study [ 18 ]. In brief, sequence raw data were demultiplexed with the demux plugin, then primers were trimmed with the cut adapt tool.…”
Section: Methodsmentioning
confidence: 99%
“…The bioinformatics analysis of the microbiome was accomplished as our study before [ 18 ]. In brief, paired-end reads were preprocessed using Cutadapt V1.18 software [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…44 In addition, Cu based NMs exhibited a higher crop diseases and pests control efficiency than did other NMs (e.g., SiO 2 , TiO 2 , ZnO, FeO, MnO, and carbon based NMs). 39,45,46 Cu based commercial pesticides have been used in agriculture for several decades, over 9.1 million pounds of Cu based pesticide were applied to agricultural land in 2018. 47 The applied Cu accumulated in agricultural soils at concentrations of 38.14-586.21 mg kg −1 , and induced ecological and human health risks.…”
Section: Cu Based Nmsmentioning
confidence: 99%
“…The optimized rhizosphere soil bacterial community enhanced ISR in tomatoes. 45 There are limited studies that have investigated the activation of ISR in crops because NMs are normally applied to crops by foliar spray. However, Tian et al (2020) revealed that foliar applied SiO 2 NMs altered the metabolite profiles in Brassica chinensis L. rhizosphere soil.…”
Section: Activation Of Host Resistance For Pathogens and Pestsmentioning
confidence: 99%